Survivors of restructuring : an analysis of the impacts on psychological well-being and work commitment : a thesis presented in partial fulfillment of the requirements for the degree of Masters of Arts in Psychology at Massey University - Berkett, Rachel (Massey University, 1998)
Downsizing remains a popular management technique for restructuring organisations. This is despite evidence that, by itself, downsizing often fails to deliver promised benefits and can result in a range of other problems. In the prior literature, little effort has been focused on the people that remain within the organisation, the 'survivors', even though these are the very people who will carry the organisation forward. The present study was designed to examine the impacts of organisational restructuring on these survivors. Specifically, the impacts restructuring has on employees' work commitment and psychological well-being. A total of 98 employees of a large meat processing company participated in the study, which used a questionnaire-based methodology and had an overall response rate of 21%. The results did not identify a relationship between work commitment and psychological well-being, but due to various explanations, this result is not necessarily definitive. On the other hand, the results did indicate that restructuring had clear impacts on employees' levels of work commitment and psychological well-being and that these impacts slowly diminish over time. Site specific data was non-significant, but information on several demographic variables (for example, age, education level, income status, gender, the number of dependents a person has, their length of tenure with the company, and the number of years the employee had worked in their present job) provided very pertinent information.
Keywords: Industrial psychology; Downsizing of organizations; Employee motivation; Employee morale; New Zealand; Restructuring